Effects of grazing on ecosystem structure and function of alpine grasslands in Qinghai–Tibetan Plateau: a synthesis. Issue 1 (4th January 2017) - Lu, Xuyang; Kelsey, Kathy C.; Yan, Yan; Sun, Jian; Wang, Xiaodan; Cheng, Genwei; Neff, Jason C.
Abstract: Humans have grazed on the Qinghai–Tibetan Plateau (QTP) for many thousands of years. In recent decades, the intensity of grazing has increased and several new management strategies have been put into place to address the resulting changes in rangeland condition. Effective management of grazing activities in this region requires understanding the impact of livestock grazing across the diverse array of alpine grassland ecosystems present in the QTP, but recent studies have identified a number of critical uncertainties in the ecological science that underlies these management principles. To address these uncertainties, we carried out a synthesis analysis of the effect of livestock grazing on 26 indicators of ecosystem structure and function based on 61 studies from 88 independent research sites within the QTP. Our synthesis results indicate that livestock grazing exerts complex controls on ecosystem structure and function, which vary according to local landscape characteristics. We found that grazing contributes to greater plant species diversity (Shannon–Wiener index, Simpson dominance index, and Pielou evenness index significantly increased 0.18, 0.05, and 0.03, respectively, due to grazing), but decreased aboveground biomass (47.15%), soil organic carbon (12.41%), soil total nitrogen (12.75%), and microbial biomass carbon (9.42%). Further, ecosystem function is controlled by interactions between grazing and other landscape characteristics such as elevation and mean annual temperature. The management regime currently in place in the QTP, which involves complete exclusion of grazing in some areas, can have variable effects on grassland health. Therefore, the complexity of these responses is an indication that livestock and grassland management may benefit from a more nuanced management regime than is currently utilized in the QTP.